Topical bromfenac for prevention and treatment of cystoid macular edema following cataract surgery: a review - Sheppard JD (Dove Medical Press, 2016)
John D Sheppard1,2 1Virginia Eye Consultants, 2Department of Ophthalmology, Eastern Virginia Medical School, Norfolk, VA, US Abstract: Topical nonsteroidal anti-inflammatory drugs (NSAIDs) and corticosteroids, alone or in combination, have historically been used off label in the US to prevent and treat postoperative cystoid macular edema (CME). This literature review presents available data on the use of bromfenac 0.07% or 0.09% to prevent and treat CME following cataract surgery. Bromfenac is an NSAID approved to treat postoperative inflammation and reduce ocular pain following cataract surgery. Few cases of clinical CME were observed with bromfenac use in a total of 19 reviewed studies. There were no significant differences in CME incidence between bromfenac and corticosteroid-treated patients or between bromfenac- and bromfenac plus corticosteroid-treated patients. Bromfenac demonstrated comparable efficacy to other NSAIDs in preventing CME. Compared with corticosteroids, bromfenac alone or plus a corticosteroid showed similar or better efficacy in minimizing changes in retinal thickness and macular volume. In diabetic cataract surgery patients, bromfenac was comparable or superior to corticosteroids for minimizing changes in retinal thickness; also, combination therapy with bromfenac and corticosteroids may be associated with smaller changes in foveal thickness, macular thickness, and macular volume versus monotherapy with either treatment alone in this patient population. In two randomized, double-masked, placebo-controlled clinical trials with bromfenac 0.07%, CME was reported as an adverse event in 0.5% and 1.5% of patients receiving bromfenac and placebo, respectively. In an analysis of four placebo-controlled trials with bromfenac 0.09%, macular edema was reported in 0.7% and 1.4% of patients receiving bromfenac and placebo, respectively. When evaluated as treatment for acute or chronic CME, bromfenac was associated with improvement in visual acuity and reduction in retinal thickness, but few studies are available. Overall, published data suggest that bromfenac is safe and effective when used to prevent or treat CME. Large-scale placebo-controlled trials and greater standardization of CME measures are needed to establish optimal bromfenac regimens for the prophylaxis and treatment of CME following cataract surgery. Keywords: anti-inflammatory agents, nonsteroidal, NSAID, bromfenac, cystoid macular edema, Irvine–Gass syndrome